RECONSTITUTION OF EUKARYOTIC LAGGING STRAND DNA REPLICATION - Balakrishnan, Lata (2010)
Eukaryotic DNA replication is a complex process requiring the proper functioning of a multitude of proteins to create error-free daughter DNA strands and maintain genome integrity. Even though synthesis and joining of Okazaki fragments on the lagging strand involves only half the DNA in the nucleus, the complexity associated with processing these fragments is about twice that needed for leading strand synthesis. Flap endonuclease 1 (FEN1) is the central component of the Okazaki fragment maturation pathway. FEN1 cleaves flaps that are displaced by DNA polymerase δ (pol δ), to create a nick that is effectively joined by DNA ligase I. The Pif1 helicase and Dna2 helicase/nuclease contribute to the maturation process by elongating the flap displaced by pol δ. Though the reason for generating long flaps is still a matter of debate, genetic studies have shown that Dna2 and Pif1 are both important components of DNA replication. Our current knowledge of the exact enzymatic steps that govern Okazaki fragment maturation has heavily derived from reconstitution reactions in vitro, which have augmented genetic information, to yield current mechanistic models. In this review we describe both the design of specific DNA substrates that simulate intermediates of fragment maturation and protocols for reconstituting partial and complete lagging strand replication.